1977
DOI: 10.1111/j.1745-4565.1977.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fumigants on Food Quality

Abstract: Fumigants are used to prevent pest infestations in food and other stored commodities. The quality of the commodity may be affected by fumigant treatment in several ways. Residues of unchanged fumigant may remain in the commodity. Reaction of the individual chemical components of the commodity with the fumigant may alter its chemical or physical properties, thus resulting in changes in flavor, taste, odor, nutritional value or processing qualities. Methyl bromide, ethylene dibromide, ethylene dichloride, carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Chattha et al (2014) conducted a study on the effect of storage methods on wheat and found that the deterioration rate in wheat grain varies depending on the type of structure, geographical location, and storage period. The various fumigation chemicals have also shown their impact on insect infestation, microbiota, nutritional aspects, and quality characteristics, but little is known about the impact of phosphine fumigant on the quality characteristics of wheat (Plimmer, 1977; Rajendran & Sriranjini, 2008; Solanki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chattha et al (2014) conducted a study on the effect of storage methods on wheat and found that the deterioration rate in wheat grain varies depending on the type of structure, geographical location, and storage period. The various fumigation chemicals have also shown their impact on insect infestation, microbiota, nutritional aspects, and quality characteristics, but little is known about the impact of phosphine fumigant on the quality characteristics of wheat (Plimmer, 1977; Rajendran & Sriranjini, 2008; Solanki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, targeting the total mortality of insects and targeting the higher terminal concentrations of the chemical fumigants may lead to accompanying germination deterioration of seed grains [17,18,19] and nutritional loss in stored products [20].…”
Section: Introductionmentioning
confidence: 99%
“…Grain storage managers often resort to using fumigants and other chemicals to protect and disinfest stored wheat. However, these chemicals are known to be sorbed by the grain and to react with various components of the seed, potentially leaving unwanted residues and perhaps changing the inherent characteristics of the grain (Plimmer 1977;Bond 1984;Hwaidi et al 2015). In addition, applying fumigants during storage may affect the germination ability of the fumigated seed.…”
mentioning
confidence: 99%